Attention - Srinivasan, Narayanan; ScienceDirect eBooks; International Conference on Attention (2008 : Allahabad, India) (Amsterdam ; Boston : Elsevier, 2009)
This well-established international series examines major areas of basic and clinical research within neuroscience, as well as emerging and promising subfields. This volume explores interdisciplinary research on Attention and interaction of Attention with other cognitive processes including perception, learning, and memory. The papers cover major research on attention in Cognitive Neuroscience and Cognitive Psychology. The volume presents recent advances on attention including binding, dynamics of attention, attention and perceptual organization, attention and consciousness, emotion and attention, development of attention, crossmodal attention, computational modeling of attention, control of actions, attention and memory, and meditation.
1. Attention and competition in figure-ground perception / M.A. Peterson and E. Salvagio -- 2. Perceptual organization and visual attention / R. Kimchi -- 3. Long-range neural coupling through synchronization with attention / G.G. Gregoriou, S.J. Gotts, H. Zhou and R. Desimone -- 4. Visual streams and selective attention / J.M. Brown -- 5. Covert attention effects on spatial resolution / M. Carrasco and Y. Yeshurun -- 6. Focused and distributed attention / N. Srinivasan, P. Srivastava, M. Lohani and S. Baijal -- 7. functional architecture of divided visual attention / K. Shapiro -- 8. Practice begets the second target: task repetition and the attentional blink effect / C. Nakatani, S. Baijal and C. van Leeuwen -- 9. Using biologically plausible neural models to specify the functional and neural mechanisms of visual search / G.W. Humphreys, H.A. Allen and E. Mavritsaki -- 10. Extinction: a window into attentional competition / M.J. Riddoch, S.J. Rappaport and G.W. Humphreys -- 11. adaptive workspace hypothesis about the neural correlates of consciousness: insights from neuroscience and meditation studies / A. Raffone and N. Srinivasan -- 12. Cognitive maps and attention / O. Hardt and L. Nadel -- 13. remains of the trial: goal-determined inter-trial suppression of selective attention / A. Lleras, B.R. Levinthal and J. Kawahara -- 14. Attentional limits and freedom in visually guided action / J.T. Enns and G. Liu -- 15. Attention for action during error correction / K.M. Sharika, S. Ray and A. Murthy -- 16. Explaining the Colavita visual dominance effect / C. Spence -- 17. Development of attentional processes in ADHD and normal children / R. Gupta and B.R. Kar -- 18. Interaction of language and visual attention: evidence from production and comprehension / R.K. Mishra -- 19. Interactions of attention, emotion and motivation / J. Raymond -- 20. Human social attention / E. Birmingham and A. Kingstone.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Attention; Cognitive neuroscience; Attention; Cognitive neuroscience; Attention; Cognitive Science; Electronic books